The Relationship between Psychological/Mentally with Anxiety Level of Pre-Caesarean Section Patients in dr. M. Yunus Hospital Bengkulu - Vellyza Colin; Santoso Ujang Effendi; Desna Pranata Leoni (Sekolah Tinggi Ilmu Kesehatan Tri Mandiri Sakti Bengkulu, 2018)
The purpose of this study was to study the relationship between psychological/mental factors with the level of anxiety in pre-caesarean section patients treated in the C1 Mawar Midwifery Ward, dr. M. yunus Bengkulu. The design of this research was Cross Sectional. The population in this study was pre-caesarean section patients treated in C1 Mawar obstetric ward RSUD dr. M. Yunus Bengkulu was 30 people, while the sampling in this study was using accidental sampling techniques and data collection researchers used questionnaires through interviews or primary data. The results of chi-square statistical test showed that there were 9 patients (30.0%) with feelings of guilt or guilt and 21 patients (70.0%), 12 people (40.0%) with psychological trauma or guilt and 18 people (60.0%) did not experience psychological trauma, 11 people (36.7%) with moderate anxiety and 19 people (63.3%) with mild anxiety. There was a significant relationship between psychological / mental factors with the level of anxiety in patients with pre-caesarean section in the C1 Mawar Obstetrics Room, RSUD dr. M. Yunus Bengkulu, with a close relationship category. It was recommended for nurses in RSUD dr. M Yunus Bengkulu to provide counseling and explanation about feelings of guilt or guilt and psychic trauma to mother that went through pre-caesarean section to reduce anxiety levels. Keywords: anxiety level, patient, psychological/mental, pre- caesarean sectio